Composição química das águas pluviais e deposição atmosférica anual na bacia do Alto Sorocaba (SP) - Conceição, Fabiano Tomazini da [UNESP]; Sardinha, Diego de Souza [UNESP]; Navarro, Guillermo Rafael Beltran [UNESP]; Antunes, Maria Lúcia Pereira [UNESP]; Angelucci, Vivian Andréa [UNESP] (Sociedade Brasileira de Química, 2011)
Two sampling points were chosen and forty samples were collected between January and December 2006 at Alto Sorocaba basin. The rainwater pH varied from 5.46 to 6.36 (Ibiúna) and 5.26 to 6.81 (Itupararanga), being Ca2+ the main ion responsible for controlling the rainwater pH. The ionic concentrations decreased in the following order: Ca2 +>Na+> Mg2+>K+ for cations and SO4(2-)>HCO3->NO 3->Cl- >PO4(3-) for anions. The annual atmospheric deposition appeared to be controlled mostly by following sources: mining activities and cement factories (Ca2+ and HCO3-), natural soil dust (Na+, Mg2+ and HCO3-), fossil fuel burning (SO4(2-)) and agriculture activities (K+, NO3- and PO4(3-)).
Rainwater chemical composition and annual atmospheric deposition at Alto Sorocaba basin (SP)
Keywords: watershed; ionic composition; air pollution